Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get immediate answers to your questions from a wide network of experienced professionals on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the equation \(\sqrt{3x + 3} - 1 = x\), let's follow a step-by-step approach:
1. Isolate the square root term:
[tex]\[ \sqrt{3x + 3} = x + 1 \][/tex]
2. Square both sides to eliminate the square root:
[tex]\[ (\sqrt{3x + 3})^2 = (x + 1)^2 \][/tex]
Simplifying both sides, we get:
[tex]\[ 3x + 3 = (x + 1)^2 \][/tex]
Expanding the right side:
[tex]\[ 3x + 3 = x^2 + 2x + 1 \][/tex]
3. Move all terms to one side to form a quadratic equation:
[tex]\[ 3x + 3 - 3x = x^2 + 2x + 1 - 3x - 3 \][/tex]
Simplifying, we get:
[tex]\[ 0 = x^2 - x - 2 \][/tex]
Rearranging, we have:
[tex]\[ x^2 - x - 2 = 0 \][/tex]
4. Factorize the quadratic equation:
We look for two numbers that multiply to \(-2\) and add up to \(-1\). These numbers are \(-2\) and \(1\). Thus, the quadratic can be factored as:
[tex]\[ (x - 2)(x + 1) = 0 \][/tex]
5. Find the roots of the factored equation:
Setting each factor to zero gives:
[tex]\[ x - 2 = 0 \quad \text{or} \quad x + 1 = 0 \][/tex]
Solving these, we find:
[tex]\[ x = 2 \quad \text{or} \quad x = -1 \][/tex]
6. Check for extraneous solutions:
- For \(x = 2\):
[tex]\[ \sqrt{3(2) + 3} - 1 = 2 \][/tex]
Simplifying the left-hand side:
[tex]\[ \sqrt{6 + 3} - 1 = 2 \implies \sqrt{9} - 1 = 2 \implies 3 - 1 = 2 \implies 2 = 2 \quad (\text{True}) \][/tex]
- For \(x = -1\):
[tex]\[ \sqrt{3(-1) + 3} - 1 = -1 \][/tex]
Simplifying the left-hand side:
[tex]\[ \sqrt{-3 + 3} - 1 = -1 \implies \sqrt{0} - 1 = -1 \implies 0 - 1 = -1 \implies -1 = -1 \quad (\text{True}) \][/tex]
Since both values satisfy the original equation, the solutions are \(x = -1\) and \(x = 2\).
Thus, the correct answer is:
#### A. -1 and 2
1. Isolate the square root term:
[tex]\[ \sqrt{3x + 3} = x + 1 \][/tex]
2. Square both sides to eliminate the square root:
[tex]\[ (\sqrt{3x + 3})^2 = (x + 1)^2 \][/tex]
Simplifying both sides, we get:
[tex]\[ 3x + 3 = (x + 1)^2 \][/tex]
Expanding the right side:
[tex]\[ 3x + 3 = x^2 + 2x + 1 \][/tex]
3. Move all terms to one side to form a quadratic equation:
[tex]\[ 3x + 3 - 3x = x^2 + 2x + 1 - 3x - 3 \][/tex]
Simplifying, we get:
[tex]\[ 0 = x^2 - x - 2 \][/tex]
Rearranging, we have:
[tex]\[ x^2 - x - 2 = 0 \][/tex]
4. Factorize the quadratic equation:
We look for two numbers that multiply to \(-2\) and add up to \(-1\). These numbers are \(-2\) and \(1\). Thus, the quadratic can be factored as:
[tex]\[ (x - 2)(x + 1) = 0 \][/tex]
5. Find the roots of the factored equation:
Setting each factor to zero gives:
[tex]\[ x - 2 = 0 \quad \text{or} \quad x + 1 = 0 \][/tex]
Solving these, we find:
[tex]\[ x = 2 \quad \text{or} \quad x = -1 \][/tex]
6. Check for extraneous solutions:
- For \(x = 2\):
[tex]\[ \sqrt{3(2) + 3} - 1 = 2 \][/tex]
Simplifying the left-hand side:
[tex]\[ \sqrt{6 + 3} - 1 = 2 \implies \sqrt{9} - 1 = 2 \implies 3 - 1 = 2 \implies 2 = 2 \quad (\text{True}) \][/tex]
- For \(x = -1\):
[tex]\[ \sqrt{3(-1) + 3} - 1 = -1 \][/tex]
Simplifying the left-hand side:
[tex]\[ \sqrt{-3 + 3} - 1 = -1 \implies \sqrt{0} - 1 = -1 \implies 0 - 1 = -1 \implies -1 = -1 \quad (\text{True}) \][/tex]
Since both values satisfy the original equation, the solutions are \(x = -1\) and \(x = 2\).
Thus, the correct answer is:
#### A. -1 and 2
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.